The Determining Factors of Quality of Life in Chronic Kidney Disease Patients with Hemodialysisin Hospitals: A Literature Review - Wahyuni, Ni Wayan Sri; Kamaryati, Ni Putu; Rismawan, Made; Suantika, Putu Inge Ruth (Babali Nursing Research, 2025)
Introduction: Patients with chronic renal failure undergoing hemodialysis often experience a decline in quality of life. This decline is due to challenges in accepting their condition, the physical and emotional impact of treatment, and significant lifestyle changes. Maintaining or improving quality of life is essential for these patients to manage their condition effectively and live well. Methods: This study employed a literature review design, adhering to the PRISMA checklist for study selection. The review utilized five journal databases: ScienceDirect, EBSCO, PubMed, Neliti, and Google Scholar, with keywords aligned with MeSH terms: "quality of life," "chronic renal failure," "determinants," and "hemodialysis." The inclusion criteria encompassed articles published between 2015 and 2024 in English or Indonesian. A total of 15 eligible articles were included in the analysis. Results: The literature review identified several factors influencing the quality of life in hemodialysis patients. These included demographic factors such as age, gender, and education; clinical aspects like hemodialysis duration, medication adherence, complications, and comorbidities; psychological factors such as depression; and social determinants like family support and income. Nutritional status and hemoglobin levels were also significant contributors. Conclusion: This study identified several factors affecting the quality of life of hemodialysis patients, including hemodialysis duration, medication adherence, age, gender, education, occupation, family support, nutritional status, depression, hemoglobin levels, and comorbidities. Future research should explore additional factors not covered in this review to understand better the most influential determinants of quality of life in patients with chronic kidney failure.